Supercritical extraction of volatile and fixed oils from Petroselinum crispum L. seeds: chemical composition and biological activity. Issue 7 (3rd April 2022) - Piras, A.; Porcedda, S.; Falconieri, D.; Fais, A.; Era, B.; Carta, G.; Rosa, A.
Abstract: The supercritical fluid extraction (SFE) of volatile and fixed oil from milled parsley ( Petroselinum crispum L.) seeds, using CO2 as solvent, is presented in this study. Extraction experiments were carried out in two steps: at pressures of (90 or 300) bar and temperature of 40 °C. The first extraction step, performed at 90 bar, produced a volatile fraction mainly formed by apiole (82.1%) and myristicin (11.4%). The volatile oil yield was 2.6% by weight of the charge. The second extraction step, carried out at 300 bar produced a fixed oil at a yield of 0.4% by weight. The most represented fatty acids in P. crispum fixed oil were 18:1 n-12 (49.9%), 18:2 n-6 (18.2%), 18:1 n-9 (11.8%), and 16:0 (7.4%). In particular, the unsaturated fatty acids 18:1 n-12 and 18:1 n-9 averaged 182.2 mg/g and 92.1 mg/g of oil extract, respectively. The quality of the oils extracted by SFE, in terms of its chemical composition, was compared to the oils obtained by hydrodistillation (HD) in a Clevenger apparatus and by solvent extraction (SE) using n -hexane in a Soxhlet apparatus. The antioxidant properties were determined by means of the ABTS assay. The results indicated that the fixed oil possessed low antioxidant activity (EC50 = 0.4 mg/mL) and the volatile oil had no antioxidant activity. The total phenolic content, expressed as concentration of gallic acid (gallic acid equivalent, GAE), of the fixed oil was 1.5 mg/g. The fixed oil found to have inhibitory effects against α-glucosidase, the volatile oil is active on acetylcholinesterase (AChE), tyrosinase, and α-glucosidase. Both samples have weak inhibitory activity on α-amylase and no activity on butyrylcholinesterase (BChE). Graphical Abstract: